KEBIJAKAN DIVIDEN MEMEDIASI PENGARUH STRUKTUR MODAL TERHADAP NILAI PERUSAHAAN - Kusumarini, Ni Md Chintya Pramudya; Abundanti, Nyoman (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.13.NO.01.TAHUN.2024, 2024)
The purpose of this study is to determine the significance of the effect of capital structure on firm value mediated by dividend policy. This research was conducted on companies in the consumer goods industry sector on the Indonesia Stock Exchange for the 2018-2021 period. The number of samples used in this study were 21 companies which were determined by the purposive sampling method. The analytical technique used in this research is path analysis and using SPSS software. The results showed that capital structure had a significant positive effect on firm value, capital structure had an insignificant positive effect on dividend policy, dividend policy had an insignificant positive effect on firm value, and dividend policy was not able to mediate the effect of capital structure on firm value.